Physical Interaction between Curcumin and Paracetamol in the Binary Mixture and Its Impact on the Solubility of Curcumin - Fikri Alatas; Susi Sunarty Sigalingging; Citra Permata Sari; Fahrauk Faramayuda; Sundani Nurono Soewandhi (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2024)
Curcumin, found in turmeric (Curcuma longa L.), is a pharmacologically active component with hepatoprotective properties. In addition to alleviating pain, the synergistic effects of paracetamol protect the liver from harm. Oral solid dose formulations of curcumin have low bioavailability due to its low solubility. This study aims to characterize the physical interactions that occur in the binary mixture of curcumin and paracetamol and to determine its impact on the solubility of curcumin. The curcumin-paracetamol binary mixture with a 1:1 stoichiometric ratio was prepared by a wet grinding method with the addition of a small amount of ethanol. The characterization of the physical interactions in the wet milling result was carried out using a powder X-ray diffractometer (PXRD) and a differential scanning calorimeter (DSC). Evaluation of physicochemical properties was carried out by testing its solubility in water and its dissolution rate in 40% v/v ethanol. The PXRD pattern of the curcumin-paracetamol milling result did not show any new peaks that were different from the typical peaks of the two components (curcumin form I and paracetamol form 1). The thermogram DSC of the binary mixture curcumin-paracetamol (1:1) only showed one wide endothermic transition at 151.2Â°C which is below the melting point of curcumin and paracetamol which is thought to be the melting point of the eutectic mixture of curcumin-paracetamol (1:1). The solubility of curcumin from the curcumin-paracetamol (1:1) milled binary mixture was 8.3-folds higher than that of pure curcumin. The dissolution rate of curcumin from the wet milling of the curcumin-paracetamol binary mixture (1:1) was also faster than that of pure curcumin. The research results can be concluded that wet milling of the binary mixture of curcumin-paracetamol (1:1) with a little ethanol shows a physical interaction with the formation of a simple eutectic mixture between the two substances which has an impact on increasing the solubility and dissolution rate of curcumin.